Effect of actual and perceived violence on internal migration: Evidence from Mexico's drug war - Amilcar O. Fernández Domínguez (IZA Journal of Development and Migration, 2020)
According to the Organisation for Economic Co-operation and Development (OECD), violence should be considered by examining both actual and perceived crime. However, the studies related to violence and internal migration under the Mexican drug war episode focus only on one aspect of violence (perception or actual), so their conclusions rely mostly on limited evidence. This article complements previous work by examining the effects of both perceived and actual violence on interstate migration through estimation of a gravity model along three 5-year periods spanning from 2000 to 2015. Using the methods of generalized maximum entropy (to account for endogeneity) and the Blinder-Oaxaca decomposition, the results show that actual violence (measured by homicide rates) does affect migration, but perceived violence explains a greater proportion of higher average migration after 2005. Since this proportion increased after 2010 and actual violence, the results suggest that there was some adaptation to the new levels of violence in the period 2010-2015.
Keywords: Z10; C33; J10; 330; homicide rates; gravity model; interstate migration